2010
DOI: 10.1016/j.juro.2009.11.057
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for Pediatric Stone Disease in United States, 2002–2007

Abstract: Children with stones now account for 1 in 685 pediatric hospitalizations in the United States. Surprisingly more than half of the patients are younger than 13 years at hospitalization. Similar to findings in adults, white race and occurrence in late summer months increase the risk of stone hospitalization. However, male gender and geographic location in the Southeast are not risk factors, demonstrating the unique aspects of pediatric stone hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(77 citation statements)
references
References 21 publications
1
64
0
9
Order By: Relevance
“…These criteria likely capture nearly all clinically important stone events because of the acute nature of stone episodes that require emergency evaluation, hospital admission, and/or surgery (8,9,15). The first qualifying claim defined the date of presentation.…”
Section: Kidney Stone Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…These criteria likely capture nearly all clinically important stone events because of the acute nature of stone episodes that require emergency evaluation, hospital admission, and/or surgery (8,9,15). The first qualifying claim defined the date of presentation.…”
Section: Kidney Stone Incidencementioning
confidence: 99%
“…Historically, the prevalence of nephrolithiasis has been highest among middle-aged, white men (5,6). However, over the last 25 years, there were smaller changes in the prevalence among men than women, and there have been reports of increasing frequency of nephrolithiasis among children and adolescents (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In adults, kidney stones are associated with hypertension and chronic kidney disease, as well as an increasing financial burden (1-5). Although relatively rare in the pediatric population, recent data regarding incidence (6), cost (5), and inpatient hospitalization rates (7,8) for children with kidney stones bring into sharp focus the need to gain a better understanding of the metabolic underpinnings as well as environmental contributors to pediatric nephrolithiasis so that we may improve on strategies for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the risk of nephrolithiasis in age group of 14 to 18 years is 10 times greater. The hospitalization rate also follows the same pattern (9,12,21,22). In a Tasian study, the greatest change belonged to 15 to 19 year olds, and the incidence of nephrolithiasis increased by 26% per five years.…”
Section: Incidence and Trendmentioning
confidence: 70%
“…On the other hand, there has been a change regarding the gender of patients. Previous reports demonstrated that nephrolithiasis was usually more common in boys than in girls, but recent studies have shown a noticeable rising incidence of nephrolithiasis in girls and some studies even substantiated that nephrolithiasis are more common among girls (4,9,10,12,15,16). Usually girls in the second decade are more prone to hospital administration for kidney stone (12).…”
mentioning
confidence: 99%